INFORMATION AND RESOURCE HUB OF THE EDUCATIONAL INSTITUTION: A MODEL FOR THE FORMATION OF SENIOR PUPILS’ LIFE SUCCESS - Bezruk, Kateryna (Theoretical and Methodical Problems of Children and Youth Education, 2024)
The research is devoted to the study of the problem of life success of high school students and the factors that influence its formation. The relevance of the study is due to global changes and challenges, particularly in the context of a full-scale war in Ukraine. The article emphasizes the need to adapt the education system to these conditions to promote the development of high school students. The primary purpose of the study is to theoretically investigate the information and resource hub of an educational institution as a model for the formation of life success of high school students. The article examines the main components of this model and its impact on the readiness of teachers to form the life success of senior pupils. In the study, a systematic and structural analysis of psychological, pedagogical and scientific sources on the research problem is applied. Among the theoretical methods used were analysis, synthesis, abstraction, generalization, specification, and systematization to study the conditions and indicators of an educational institution’s information and resource hub as a model for the formation of life success of senior pupils. The empirical methods were questionnaires (offline and online), observation, and blitz surveys. All of these methods were used to determine the readiness of teachers to form the life success of high school students. The study results showed that creating an open interactive space contributes to more effective cooperation between teachers and high school students. The information competence of teachers, which is enhanced by the information and resource hub, is an essential factor in this process. The generalized empirical data allow us to substantiate the effectiveness of creating an information and resource hub as a model for shaping the life success of high school students and confirm that creating an open, interactive space where teachers can interact and share experiences contributes to the formation of life success of high school students and increases the prestige of the institution among students, parents, teachers and partners of educational institutions.